Sex differentially affects pro-inflammatory cell subsets in adipose tissue depots in a diet induced obesity model - Lisa T. Schuetz; Gayel Duran; Paulien Baeten; Daphne Lintsen; Doryssa Hermans; Sarah Chenine; Janne Verreycken; Tim Vanmierlo; Kristiaan Wouters; Bieke Broux (Biology of Sex Differences)
Abstract Obesity is a growing pandemic that increases the risk for cardiovascular diseases, type 2 diabetes, and particularly in women also the risk of cancer and neurodegenerative disorders such as dementia and multiple sclerosis. Preclinical studies on obesity focus on male mice as they gain bodyweight faster and show a clear pro-inflammatory phenotype. Here, using male and female mice, we induced obesity by feeding a high fat diet (HFD), and compared adipose tissue (AT) inflammation at the same adiposity stage (% AT/bodyweight) between both sexes. Doing so, we identified that female mice show an increase in the number of pro-inflammatory immune cells in the visceral AT at a lower adiposity stage than male mice, but the effect of HFD is diminished with higher adiposity. Interestingly, only female mice showed an increase in immune cells in the subcutaneous AT after HFD feeding. Nonetheless, we found that pro-inflammatory cytokines in blood plasma mirror the inflammatory stage of the visceral AT in both male and female mice. Uniquely in male mice, myeloid cells in the visceral AT showed a higher inflammasome activation upon HFD. In summary, we showed that adiposity differentially affects immune cells in fat depots based on sex.